2016
DOI: 10.1038/srep30715
|View full text |Cite
|
Sign up to set email alerts
|

The origin of chromosomal inversions as a source of segmental duplications in the Sophophora subgenus of Drosophila

Abstract: Chromosomal inversions can contribute to the adaptation of organisms to their environment by capturing particular advantageous allelic combinations of a set of genes included in the inverted fragment and also by advantageous functional changes due to the inversion process itself that might affect not only the expression of flanking genes but also their dose and structure. Of the two mechanisms originating inversions —ectopic recombination, and staggered double-strand breaks and subsequent repair— only the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…This is however a laborious endeavor that in the absence of a medium to high quality reference genome sequence of the species under study requires the availability of either other genomic resources such as BAC libraries to narrow down the region under scrutiny, or a good reference genome of a relatively closely related species to use as a guide. The number of polymorphic inversions with breakpoints molecularly characterized is still scanty for Drosophila species4567891011121314. Only in D. melanogaster with one of the best reference genomes, the availability of population genome-wide datasets has allowed to bioinformatically identify the breakpoints of nine polymorphic inversions1516171819.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is however a laborious endeavor that in the absence of a medium to high quality reference genome sequence of the species under study requires the availability of either other genomic resources such as BAC libraries to narrow down the region under scrutiny, or a good reference genome of a relatively closely related species to use as a guide. The number of polymorphic inversions with breakpoints molecularly characterized is still scanty for Drosophila species4567891011121314. Only in D. melanogaster with one of the best reference genomes, the availability of population genome-wide datasets has allowed to bioinformatically identify the breakpoints of nine polymorphic inversions1516171819.…”
mentioning
confidence: 99%
“…Moreover, the molecular structure of these inversions breakpoints and of those of one inversion of the O chromosome (Muller’s E element)11 has also revealed that the staggered-breaks mechanism is probably the most frequently used mechanism to generate inversions in this species. Finally, the comparative analysis of the breakpoint regions of the D. subobscura polymorphic inversions across the Drosophila genus has revealed that some of these regions have been multiply disrupted121314.…”
mentioning
confidence: 99%
“…In addition, duplicate regions in these events range from a few hundred base pairs to about 8 Kbp (see Table 1), encompassing whole and partial genes in some of these duplications. However, no dose effect or generation of new transcripts was detected in the analyses [61,[84][85][86][87].…”
Section: Inversion Origin Via Staggered Breaks and Repair By Non-homomentioning
confidence: 99%
“…These inversions give rise to the complex arrangements E 1 + 2 , E 1 + 2 + 9 , E 1 + 2 + 9 + 3, and E 1 + 2 + 9 + 12 . These chromosome constitutions, besides providing a great system for the analysis of the mechanisms of origin of inversions, also provide a basis for studying the reuse of the inversion breakpoints at the molecular level [61,[85][86][87].…”
Section: Inversion Origin Via Staggered Breaks and Repair By Non-homomentioning
confidence: 99%
See 1 more Smart Citation